The absolute number of T lymphocyte subsets is beneficial for differential diagnosis of myelodysplastic syndrome with pure red cell aplastic anemia: a case report and review of the literature - Zhang, Liangjun; Zhong, Huixiu (Frontiers in Immunology, 2025)
The two diseases of myelodysplastic syndrome (MDS) and pure red cell aplasia (PRCA) are independent of each other and can be linked in some cases. Their diagnosis and differential diagnosis are very confusing. Therefore, in order to understand the relationship between MDS and PRCA and improve the diagnosis and treatment of MDS in patients with PRCA, we present a case study of a 71-year-old male patient with anemia. The result of the morphological examination of bone marrow, whole-genome microarray, and bone marrow biopsy all supported the diagnosis of MDS at the first clinical diagnosis. Azacitidine and venetoclax chemotherapy were given to the patient. However, the treatment is not effective, and the absolute number of T lymphocyte subsets decreased gradually during treatment. Then, the treatment plan was changed to cyclosporine A plus prednisone for immune regulation. The absolute number of T lymphocyte subsets and hemoglobin (Hb) rose rapidly, and the final diagnosis of the patient was MDS with PRCA. To improve the ability to diagnose MDS with PRCA, we should combine it with the absolute number of T lymphocytes to monitor efficacy evaluation during treatment, which contributes to the differential diagnosis of MDS with PRCA.